THE INFLUENCE OF ORGANIZATIONAL SOCIALIZATION ON EMPLOYEE TURNOVER INTENTION AT BRI MANADO BRANCH OFFICE - Umboh, Julvan Jermia (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
The effective of human resource is important to help the organization sustainability in competition. Good human resources are supported by the skilled employees and creative employees. To get creative employees and professional employees, organizations need to pay attention for producing a good working environment between the organization and employees. The domains of Organizational Socialization are Training, Understanding, Coworker Support, and Future Prospects. The purpose of this study was to examine how Organizational Socialization influences on employee Turnover Intention. Use multiple regression models to answer the research problem. The target population of this study consisted of employees of BRI Manado. Data were collected from 100 employees of BRI Manado. The hypothesis testing, this research conduct a conclusion of there is a significant influence of Training, Understanding, Coworker Support, Future Prospect simultaneously on employee Turnover Intention and there is a significant influence of Training, Understanding, Coworker Support and Future Prospect of Organizational Socialization partially on employee Turnover Intention. This study reveals that Coworker Support is the most significant credibility source to influence employee Turnover Intention. This means that when employees make a decision quit or stay with the job, they prefer to think about their environment and the other coworker of workplace. Keywords: organizational socialization, employee turnover intention